Dextran sulfate inhibits acute Toxoplama gondii infection in pigs. Issue 1 (December 2016) - Kato, Kentaro; Murata, Yuho; Horiuchi, Noriyuki; Inomata, Atsuko; Terkawi, Mohamad; Ishiwa, Akiko; Ogawa, Yohsuke; Fukumoto, Shinya; Matsuhisa, Fumikazu; Koyama, Kenji
Abstract Background Toxoplasma gondii is a highly prevalent protozoan that can infect all warm-blooded animals, including humans. Its definitive hosts are Felidae and its intermediate hosts include various other mammals and birds, including pigs. It is found in the meat of livestock which is a major source of human infection. Hence the control of toxoplasmosis in pigs is important for public health. We previously showed that dextran sulfate (DS), especially DS10 (dextran sulfate MW 10 kDa), is effective againstT. gondii infection both in vitro and in mice. In this study, we asked whether DS affectsT. gondii infection of pigs, one of the main animal sources of toxoplasmosis transmission to humans. Methods Fourteen-day-old male pigs (n = 10) were infected withT. gondii and then immediately treated with different doses of DS10; clinical, pathological, and immunological analyses were performed 5 days post-infection. Results DS10 had an inhibitory effect on toxoplasmosis in pigs. Intravenous injection of DS10 prevented the symptoms of toxoplasmosis and reduced the parasite burden and inflammation induced byT. gondii infection. High-dose DS10 (500 μg per head) caused reversible hepatocellular degeneration of the liver; middle-dose DS10 (50 μg per head) was effective against toxoplasmosis in pigs without causing this side effect. Conclusions Our data suggest that middle-dose DS10 led to minimal clinical symptoms ofT. gondii infection and caused little hepatocellular degeneration in our pig model, thereby demonstrating its potential as a new treatment for toxoplasmosis. These data should be very beneficial to those interested in the control of toxoplasmosis in pigs.